Growth and Sustainability Model for Medium and Large Size Healthcare Organizations in Post-Pandemic India - Singh, Ashish Kumar (Digital Repository of Theses - SSBM Geneva, 2025)
The aim of this research is also to deepen our knowledge of crisis management in the healthcare industry. This study compares the pre- and post-COVID-19 expansion and sustainability strategies of medium- and large-sized healthcare organisations in India. It delves further into how these methods could shape healthcare in India going forward. To further understand the tactical and strategic reactions to the epidemic, this study uses a mixed-method approach, integrating quantitative survey data with qualitative findings from prior research. The sample consists of senior management and key decision-makers from hospitals and healthcare institutions across various regions of India. The study shows that healthcare institutions operated through multiple challenging situations, including insufficient resources, funding limitations, personnel shortages, and high patient demands. The crisis compelled educational institutions to adopt various strategies for crisis mitigation. Healthcare institutions implemented four main approaches to tackle the crisis, which involved accelerating digital transformation for telemedicine and AI diagnostics, along with employee safety programs, flexible work options, supply chain diversity, and agile decision-making practices. Many institutions revamped their business operations by developing new service offerings while strengthening their commitment to corporate social responsibility (CSR) in society. These strategies successfully kept organizations active throughout the pandemic while establishing resilient structures that contributed to business expansion. The implementation of digital tools and employee welfare support initiatives will have a lasting impact on healthcare development in India. Healthcare institutions must be prepared and quick to innovate, as the recent pandemic revealed the critical importance of readiness and agility in facing future management challenges in healthcare. These strategies demonstrate strong potential to enhance the sustainability and growth of healthcare facilities across India in the coming years.